DeePMD-kit v2: A software package for deep potential models - Zeng, Jinzhe; Zhang, Duo; Lu, Denghui; Mo, Pinghui; Li, Zeyu; Chen, Yixiao; Rynik, Marián; Huang, Li’ang; Li, Ziyao; Shi, Shaochen; Wang, Yingze; Ye, Haotian; et al. (The Journal of chemical physics, 2023)
DeePMD-kit is a powerful open-source software package that facilitates molecular dynamics simulations using machine learning potentials known as Deep Potential (DP) models. This package, which was released in 2017, has been widely used in the fields of physics, chemistry, biology, and material science for studying atomistic systems. The current version of DeePMD-kit offers numerous advanced features, such as DeepPot-SE, attention-based and hybrid descriptors, the ability to fit tensile properties, type embedding, model deviation, DP-range correction, DP long range, graphics processing unit support for customized operators, model compression, non-von Neumann molecular dynamics, and improved usability, including documentation, compiled binary packages, graphical user interfaces, and application programming interfaces. This article presents an overview of the current major version of the DeePMD-kit package, highlighting its features and technical details. Additionally, this article presents a comprehensive procedure for conducting molecular dynamics as a representative application, benchmarks the accuracy and efficiency of different models, and discusses ongoing developments.